Pengujian Crud Link Pada Aplikasi Linkstack Berbasis Web Menggunakan Black Box Testing - Zakiah Mutiara Anggraini (PT Jurnal Cendekia Indonesia, 2025)
Bio-link applications such as LinkStack offer a flexible and customizable personal link management solution. Testing CRUD (Create, Read, Update, Delete) functions is important to ensure the stability and reliability of the application. This study aims to test the performance of CRUD features on the web-based LinkStack application running in the Docker environment. The testing method used is manual black box testing with scenarios including registration, login, adding, editing, deleting, and displaying the link list. The test results show that all CRUD features run well, the interface is responsive, and no bugs were found during testing. In conclusion, the LinkStack application is worthy of use as a personal link management platform, with Docker support providing consistency and stability during testing. Further automated and cross-environment testing is recommended to increase the range of reliability.